Factors Influencing the Accuracy of Triage in Non-Trauma Patients by Emergency Nurses - Binsama, Salisa; Naka, Kanittha; Khupantavee, Natenapha (Princess of Naradhiwas University Journal, 2021)
The predictive study aimed to explore the accuracy of triage in non-trauma patients and its influencing factors. The participants consisted of 88 emergency nurses from all levels of hospital care, from four provinces in Southern Thailand. Data were collected by questionnaires (personal information and triage knowledge questionnaires) and patient’s triage data collection forms. The questionnaires were checked for content validity by three experts, yielding the content validity of .83 and .94. Patients’ triage data were collected from each patient’s profile after completing the treatment at the ED and were analyzed using descriptive statistics and multiple regression. The results showed that emergency nurses were able to triage non-trauma patients correctly in 72.70% and incorrectly in 27.30%. Almost half of those with triage inaccuracy were under-triage. In addition, triage knowledge and work experience at the ED could significantly predict the accuracy of triage in non-trauma patients with a coefficient of variance of 46% (p<.01). The findings of this study could be used as a guidance to improve the quality of patient triage in the ED.